2011
DOI: 10.1107/s1600536811040918
|View full text |Cite
|
Sign up to set email alerts
|

1,1′-[m-Phenylenebis(nitrilomethanylylidene)]dinaphthalen-2-ol–1,1′-[m-phenylenebis(iminomethanylylidene)]dinaphthalen-2(1H)-one (0.58/0.42)

Abstract: In the solid state the title Schiff base, 0.58C28H20N2O2·0.42C28H20N2O2, exists both as the keto–imino and as the enol–amino tautomer, which is manifested in the disorder of the H atom in the intra­molecular hydrogen-bonded ring. The naphthalene ring systems show some distortion, which is consistent with the quinoid effect. The ratio of the enol form refined to 58 (5)%. The mol­ecule has crystallographically imposed symmetry: a twofold axis passes through the central benzene ring. Crystals are built up of laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A search of the Cambridge Structural Database (CSD version 5.41, update of March, 2020; Groom et al, 2016) revealed the existence of several structurally similar bis-hydroxyimines derivatives. All of them were prepared via the condensation of the corresponding diamine and an appropriate hydroxyaldehyde (Elmali et al, 1995;Blagus & Kaitner, 2011;Popović et al, 2001;Meng et al, 2008;Wang et al, 2016;Han et al, 2015). Interestingly, although keto-enol tautamerization is a well-established phenomenon for such systems, the majority of known bis-hydroxyimines exist in enol-enol forms, except the one reported by Popović et al (2001).…”
Section: Database Surveymentioning
confidence: 99%
“…A search of the Cambridge Structural Database (CSD version 5.41, update of March, 2020; Groom et al, 2016) revealed the existence of several structurally similar bis-hydroxyimines derivatives. All of them were prepared via the condensation of the corresponding diamine and an appropriate hydroxyaldehyde (Elmali et al, 1995;Blagus & Kaitner, 2011;Popović et al, 2001;Meng et al, 2008;Wang et al, 2016;Han et al, 2015). Interestingly, although keto-enol tautamerization is a well-established phenomenon for such systems, the majority of known bis-hydroxyimines exist in enol-enol forms, except the one reported by Popović et al (2001).…”
Section: Database Surveymentioning
confidence: 99%